Inappropriate behaviours experienced by doctors while undertaking specialty training. Issue 4 (20th December 2018) - Abhary, Sotoodeh; Botti, Mari; Dhulia, Anjali; Loh, Erwin; Catford, John
Abstract : Purpose: To explore inappropriate behaviours experienced during specialty training in Australia and their implications for doctors' training experiences and outcomes. This is a subset of data from a larger study exploring experiences of doctors in Australian specialty training—a qualitative study of enablers, stressors and supports. Methods: In this qualitative study, registrars in specialist training programmes in Australia were invited and interviewed between August 2015 and August 2016. Semistructured open-ended questions were used to explore topics of relevance to their workplace, training, support service use and personal lives. Interviews were transcribed verbatim, de-identified and content and thematic analysis undertaken. Recruitment was ceased when data saturation was reached and no new themes emerged. Key themes related to inappropriate behaviours experienced during specialty training are reported in this study. Results: 17 participants were recruited (including one Indigenous and one international medical graduate). A total of six specialty training programmes across multiple states at various locations across Australia were represented in this cohort. Almost all participants reported confronting (personally experienced or witnessed) inappropriate behaviours during their training, perpetrated most commonly by senior doctors. Key themes of inappropriate behaviour that emerged were belittling and humiliation, sexually inappropriate behaviour, inappropriate behaviour as part of the 'culture' of medicine, reluctance to raise concerns due to fear of recrimination, and impacts of inappropriate behaviour. Conclusion: Varying inappropriate behaviours were experienced by doctors in specialty training, having implications for their psychological well-being. A multidimensional and multisystem approach is required in the management of this serious issue.